2011
DOI: 10.1111/j.1537-2995.2010.03023.x
|View full text |Cite
|
Sign up to set email alerts
|

Occult hepatitis B virus infection in Thai blood donors

Abstract: The majority of donors detected during routine screening, who were HBsAg negative and NAT reactive, had an occult HBV infection, thus validating the decision to introduce NAT for blood donations in Thailand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
26
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 31 publications
6
26
1
Order By: Relevance
“…Among these 29 unclassified cases, eight were from Hong Kong, four from Malaysia, four from Singapore, and 13 from Thailand (table 1). A percentage of window period infection of 2.5 and 21 was observed in Hong Kong (unpublished data) and was previously reported in Thailand 22. Therefore it may be estimated that at least 18 of the 21 HBV-seronegative/DNA-positive donors from Hong Kong and Thailand were seronegative OBIs.…”
Section: Discussionsupporting
confidence: 52%
“…Among these 29 unclassified cases, eight were from Hong Kong, four from Malaysia, four from Singapore, and 13 from Thailand (table 1). A percentage of window period infection of 2.5 and 21 was observed in Hong Kong (unpublished data) and was previously reported in Thailand 22. Therefore it may be estimated that at least 18 of the 21 HBV-seronegative/DNA-positive donors from Hong Kong and Thailand were seronegative OBIs.…”
Section: Discussionsupporting
confidence: 52%
“…To our knowledge, these cases are novel in Australia. Similar occurrences have been reported in paediatric transfusion recipients in Taiwan 7 and in blood donors in the United States 5 , 6 and Thailand 8 . They are distinct from chronic (ie, anti‐HBc positive) occult HBV infection, which is characterised by undetectable HBsAg and very low levels of HBV DNA 9 .…”
supporting
confidence: 57%
“…Taking into account these results, the NAT‐only yield rate was 0.06%. Previous studies from this region have reported HBV NAT‐yield rates from 0.005% to 0.11% . However, it should be noted that these studies used NAT with different sensitivities ranging from 3.8 to 18.8 IU/mL as well as different formats for testing, from individual donor testing to pools of 8.…”
Section: Discussionmentioning
confidence: 99%